Interventional oncology: A primer for clinicians on the role of ablation and embolization for solid tumors - Mohamed E. Abdelsalam; Kamran Ahrar; Rahul A. Sheth; Ketan Y. Shah; Steven Yevich; Varshana Gurusamy; Bruno C. Odisio; Alda L. Tam; Armeen Mahvash; Peiman Habibollahi (CA: A Cancer Journal for Clinicians, 2026)
Abstract Interventional radiology (IR) is a rapidly evolving medical field that combines advanced imaging with minimally invasive techniques for both diagnosis and treatment. Interventional oncology (IO), a subspecialty of IR, focuses on the minimally invasive, image‐guided intervention for cancer and cancer‐related conditions. IR plays an important and increasingly recognized role within the multidisciplinary care of patients with cancer, contributing meaningfully to diagnosis, therapy, and palliation. IO therapies, particularly tumor ablation and transarterial embolization, aim to target tumors directly while preserving surrounding healthy tissue. These therapies are increasingly supported by clinical guidelines and have shown favorable outcomes in cancers such as hepatocellular carcinoma, renal cell carcinoma, and metastatic colorectal cancer. This review focuses on the role of minimally invasive, image‐guided, locoregional IR therapies for patients who have cancer.